ANALYSIS OF ACTIVE COMPOUNDS IN BLOOD PLASMA OF MICE AFTER INHALATION OF CAJUPUT ESSENTIAL OIL (MELALEUCA LEUCADENDRON L.) - Muchtaridi Muchtaridi; Ami Tjiraresmi; Riska Febriyanti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
The research is intended for the determination of volatile compounds of cajuput oil (Melaleuca leucadendron L.) in a group of mice (3 mice) after inhaling 1 mL cajuput oil for 1/2, 1 and 2 hour(s). The blood plasma of three mice was collected in heparin tube, and the volatile compounds were isolated and concentrated using C-18 Solid Phase Extraction (SPE) column with methanol and bidistilled water mixture (60:40) as the solvent. The analysis was carried out by GC/MS. The results showed that there were 52 compounds in the cajuput oil, especially 1,8-cineole,a-terpineol, b-pinene, a-pinene, b-myrcene, 4-terpineol, linalool, g-terpinene, and terpinolene. The major compound identified in blood plasma of mice was 1,8-cineole. Half an hour after 1 mL inhalation of cajuput oil per mouse, the concentration of 1,8-cineole identified was 41.5 mg/mL, while 1 and 2 hours after 1 mL inhalation of cajuput oil, the level of 1,8-cineole in blood plasma of 3 mice was 646.9 mg/mL and 138.0 mg/mL in blood plasma of each mouse. Other compounds identified were a-terpineol, 4-terpineol linalool, terpenyl acetate and hydrocarbon terpenes. Concentrations of target compounds in the blood plasma were relatively in low level (mg/mL). In conclusion, the volatile compounds of 4-terpineol, linalool, a-terpineol and 1,8-cineol that identified in blood plasma of mice after inhalation of the cajuput oils might correlate with depressive characteristics of essential oil given by inhalation.Keywords: Cajuput, Essential Oils, Inhalation, SPE, GC-MS